Gas gun driven dynamic fracture and fragmentation of Ti-6Al-4V cylinders at initial temperatures between 150 K and 750 K - Jones, D; Chapman, D; Eakins, D (AIP Publishing, 2017)
We present a study on the dynamic fracture and fragmentation of Ti-6Al-4V cylinders at initial temperatures ranging from approximately 150 K to 750 K. Cylinders with an inner diameter of 50 mm and a wall thickness of 4 mm were driven into uniform axially-symmetric expansion at radial strain rates of 104 s−1 using the ogive-insert gas gun method. Diagnostics consisted of simultaneous high speed imaging and multiple points of laser velocimetry (PDV) along the length of the sample. The imaging and PDV provided a record of the expansion process, giving expansion velocity and the failure strain. Recovered fragments were examined with optical and scanning electron microscopy and electron backscatter diffraction techniques to determine the fracture mechanisms for each initial temperature. The failure strain (radial strain at first fracture) was observed to increase with temperature over the range tested, from 7.4 ± 5.2 percent at 158 K to 24.1 ± 2.4 percent at 724 K. In experiments from 158 K up to 609 K the fracture mechanism was found to be ductile tearing under mode II loading along the planes of maximum shear at 45° to the radius. At an initial cylinder temperature of 724 K the fracture mechanism transitioned to void nucleation and coalescence along adiabatic shear bands, again forming at 45° to the radial direction. The fragmentation toughness Kf was observed to also increase with temperature until the 724 K shot where there was a marked reduction, suggesting the formation of shear bands at high temperatures reduced the energy required to form fragments. The average value of Kf was 101 ± 13 MPa m1/2.